Economic Calculations of Electricity Using AC System on Residential Load - Daud, Muhammad; Hasibuan, Arnawan; Siregar, Widyana Verawaty; Setiawan, Adi (LPPM Universitas Andalas, 2022)
The research in this final project discusses the economic calculation of electrical energy consumption in a 220 VAC system at a residential load on a type 54 house. The simulation of the AC system is carried out with ETAP 12.6 software. Simulation is done by making installations with residential loads with cables that have a length according to the distance to the loads. From the ETAP simulation, it can be seen the current and line resistance values on the report manager display so that the losses and efficiency of the two systems can also be known. Based on the results of simulations and calculations, the total value of the losses that occur in the 220 VAC system is so small that it looks like 0 watts, this happens because the simulation results are shown in kWatt in the ETAP.